EFFECT OF VILLAGE LOAN AND SAVINGS ASSOCIATIONS (VSLAs) ON FARMER’S FOOD SECURITY AND INCOME IN KEBBI STATE, NIGERIA - Yahuza Garba Illo; Gindi, Abdullahi A.; Jega, Abdulsalam A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
This study assessed the effect of Village Savings and Loan Associations (VSLAs) of the PROACT program on farmers’ food security and income in Kebbi State. Primary data were collected from a total of 576 respondents comprised of 288 participating farmers and 288 non – participating farmers sampled through the multistage sampling procedure. The data were analyzed using descriptive statistics, logit regression model, and propensity score matching techniques. The PSM result on the income of participants compared with non-participants revealed an average difference in income of ₦339,816.67 which was statistically significant at p≤0.01 probability level. The result of the propensity score matching (PSM) on food security shows an average treatment effect (ATE) score of 5.90 which was significant at p≤0.01 probability level. The difference in the average food security score shows the level of contribution of VSLA to household food security of the participants. The study concluded that VSLA has improved the income and food security of the participating farmers in Kebbi State and recommended its inclusion into the agricultural program for food security and poverty reduction in the study area.